2004
DOI: 10.1021/jp037593v
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Oxygen Reduction on Pt(111) in Acid Solutions:  Intrinsic Kinetic Parameters and Anion Adsorption Effects

Abstract: Oxygen reduction reaction (ORR) kinetics in acid solutions was studied by analysis of the polarization curves obtained by rotating disk electrode method for Pt(111) in HClO 4 and H 2 SO 4 solutions. The model for ORR kinetic currents assumes that the intrinsic exchange current and Tafel slope are independent of anion adsorption. The site blocking and electronic effects of adsorbed OH (in HClO 4 ) and bisulfate (in H 2 SO 4 ) were evaluated with the adsorption isotherms incorporated in the model. The best fits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
502
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(554 citation statements)
references
References 12 publications
44
502
1
1
Order By: Relevance
“…The experimentally observed Tafel slope for the ORR on a platinum electrode is typically between 60 and 120 mV/dec. 23,24,25 While I do not want to be lured into the discussion of the exact meaning of this Tafel slope, it does suggest that the first electron transfer of the overall four electron transfer reaction is either rate-determining or directly preceding the rate-determining step. On the other hand, the DFT-based thermodynamic analysis of Nørskov et al 1 has identified the removal of oxygenated species, such as OH ads , from the Pt surface, as the thermodynamic bottleneck in the reaction scheme.…”
Section: Modelmentioning
confidence: 99%
“…The experimentally observed Tafel slope for the ORR on a platinum electrode is typically between 60 and 120 mV/dec. 23,24,25 While I do not want to be lured into the discussion of the exact meaning of this Tafel slope, it does suggest that the first electron transfer of the overall four electron transfer reaction is either rate-determining or directly preceding the rate-determining step. On the other hand, the DFT-based thermodynamic analysis of Nørskov et al 1 has identified the removal of oxygenated species, such as OH ads , from the Pt surface, as the thermodynamic bottleneck in the reaction scheme.…”
Section: Modelmentioning
confidence: 99%
“…The structure and reaction mechanism of platinum (Pt) electrocatalysts in the ORR have been studied to reveal ORR catalysis on an atomic level. [1][2][3][4][5] In recent years, core-shell electrocatalysts have drawn wide attention to improve the mass-specific activity of Pt. 6 A typical effective core-shell electrocatalyst is a gold (Au) core with a Pt shell.…”
Section: Introductionmentioning
confidence: 99%
“…Since the procedure using equation (4) is 10 simpler, this equation will be used in the following to determine the kinetic currents. Figure 3 shows some representative curves for the ORR on the different series of electrodes.…”
mentioning
confidence: 99%